Auto‐adjusted shape prior‐based interactive segmentation via point set registration. Issue 1 (1st January 2015) - Liu, Liman; Li, Kunqian; Tao, Wenbing; Liu, Haihua
Abstract : A novel object specified segmentation approach based on the auto‐adjusted shape prior by utilising the point set registration method is presented. Three steps are included in the proposed method: (i) initial segmentation, (ii) automatic shape prior adjustment by point set registration and (iii) object segmentation constrained by the adjusted shape prior. To repair the shape difference between the local targets and the given shape model, such as location, scale, rotation and local shape details, an excellent point set registration approach named coherent point drift (CPD) is adopted. The adjusted shape constraints under the coherent moving constraint implied in CPD give reliable boundary predictions. Experimental results on the ETHZ shape dataset have demonstrated the outstanding performance of the proposed method.